2020
DOI: 10.1007/s10654-020-00627-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a plant-based, high-fibre dietary pattern is related to regression of non-alcoholic fatty liver disease in an elderly population

Abstract: Dietary lifestyle intervention is key in treating non-alcoholic fatty liver disease (NAFLD). We aimed to examine the longitudinal relation between well-established dietary patterns as well as population-specific dietary patterns and NAFLD. Participants from two subsequent visits of the Rotterdam Study were included. All underwent serial abdominal ultrasonography (median follow-up: 4.4 years) and filled in a food frequency questionnaire. Secondary causes of steatosis were excluded. Dietary data from 389 items w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…Many of these effects were seemingly rather indirectly combating secretory diarrhea frequently occurring during IBD (Schiller, 1999), than directly interacting with the progression of IBD (Jonge et al, 2020). Additionally, given the high fiber in the components of HYJJ decoction and the improved gut health following ingestion of plant-based constituents (Carvalhana et al, 2012;Alferink et al, 2020), the intrinsic nature of these herb compounds was also beneficial for the gut recovery. Collectively, network pharmacological analysis demonstrated that HYJJ provided a potential therapeutic strategy for UC handling by suppressing inflammation, restoring the homeostasis of hormones and innervation, and facilitating gut motility and digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these effects were seemingly rather indirectly combating secretory diarrhea frequently occurring during IBD (Schiller, 1999), than directly interacting with the progression of IBD (Jonge et al, 2020). Additionally, given the high fiber in the components of HYJJ decoction and the improved gut health following ingestion of plant-based constituents (Carvalhana et al, 2012;Alferink et al, 2020), the intrinsic nature of these herb compounds was also beneficial for the gut recovery. Collectively, network pharmacological analysis demonstrated that HYJJ provided a potential therapeutic strategy for UC handling by suppressing inflammation, restoring the homeostasis of hormones and innervation, and facilitating gut motility and digestion.…”
Section: Discussionmentioning
confidence: 99%
“…In this pattern, components are scored as healthy if they satisfy the following criteria: (1) vegetables and fruit intake of 400 g per day, (2) added sugar intake of < 10 g per day, (3) energy percentage from fat intake < 30%, (4) energy percentage from saturated fat intake < 10%, (5) energy percentage from trans fatty acid intake is < 1%, and (6) salt intake of < 5 g per day. 37 Similarly, in the Multiethnic Cohort study, keeping a Healthy Eating Index pattern, was related with lower risks for high visceral fat and for NAFLD. 38 Moreover, in the Framingham Heart Study cohort, improved diet quality by closer adherence to Healthy Eating Index or Mediterranean diet pattern was associated with reduction in liver fat and less risk for new onset of NAFLD over 6 years of follow-up.…”
Section: Dietary Patternsmentioning
confidence: 94%
“…Furthermore, several randomised controlled studies demonstrated that a vegan diet could be more efficient for weight loss than other eating patterns including a vegetarian diet or a MedDiet [ 152 , 153 ]. Population studies such as NHANES and the Rotterdam study indicated that high adherence to a plant-based diet was associated with improvement in risk factors (IR, BMI) related to NAFLD development [ 154 , 155 ]. A cross-sectional study ( n =3279) analysed food substitution in vegetarians and found that meat eaters had a 12% greater risk of developing NAFLD than vegetarians, suggesting that replacing animal protein with plant-based protein may prevent fatty liver [ 156 ].…”
Section: Nutrition and Nafldmentioning
confidence: 99%